Comparison of Different Offline MTPA Trajectory Estimation Methods - Černelič, Jernej; Petrun, Martin (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The main goal of this paper was to analyse and compare different offline Maximum-Torque Per Ampere (MTPA) trajectory estimation methods for Interior Permanent Magnet Synchronous Machines (IPMSMs). The analysis was performed based on Finite Element Analysis (FEA) data of IPMSMs. The obtained results show that despite neglecting all the non-linearities, the analytical MTPA trajectory calculation with constant IPMSM parameters can model the MTPA trajectory with adequately small difference when compared to optimization-based calculation. Consequently, the MTPA trajectory calculation was further simplified with a piece-wise linear approximation of the trajectory, resulting in simpler MTPA reference calculation within the controller and adequately small deviations from optimal MTPA operating points.